Inventory of Shallow-Water Fouling Invertebrates of Long Island, New York - Ezra Roesch; Jack H. Rosencrans; Kent A. Hatch; Robert W. Thacker (Oceans)
Invasive marine invertebrates are increasingly recognized as a potential disturbance to coastal ecosystems. We sought to better document the taxonomic composition of subtidal communities around Long Island to obtain a baseline that can be used to monitor current and future invasions of non-indigenous species. We placed settlement blocks at 18 sites along the coast of Long Island, New York, for three months. After recovering blocks at 12 sites, we analyzed the taxonomic composition of fouling communities on the blocks. We observed 64 invertebrate and 3 algal taxa, with large variation in taxon richness among sites. Multivariate analyses revealed that although taxon composition was significantly dissimilar between north and south shores, variation in dissimilarity did not differ significantly between shores. The high variability in taxon composition observed among sites indicates that additional research is needed to expand our knowledge of invertebrate diversity in the waters surrounding Long Island. Adding more sites and replicate blocks within sites could improve future sampling designs. This research will benefit continuing efforts to monitor, manage, and prevent the establishment of marine invasive species.